IMPACTO DE LA PANDEMIA COVID-19, EN LA SALUD MENTAL DE PACIENTES QUE ACUDEN A UNA CLÍNICA PRIVADA EN VENTANILLA - Gutierrez Lima, Marisol (2020)
Objectives: The aim was to determine the impact of the COVID-19 pandemic on the mental health of patients who go to a private clinic in Ventanilla. Materials and methods: A quantitative, descriptive and cross-sectional study was carried out. The population consisted of 204 patients. The survey technique was used and the DASS-21 measurement instrument was used, which measures the level of depression, anxiety and stress, which is composed of 21 items and 3 factors. Results: As for the participants, the minimum age was 18 years and the maximum 85 years, the mean age being 39.51 years. In relation to sex, 116 are female (56.9%) and 88 are male (43.1%). Regarding the mental health of the participants, the normal level predominated with 23% (n = 47), followed by the moderate level in 21.6% (n = 44), severe with 21.1% (n = 43), mild in 17.6% (n = 36) and extremely severe in 16.7% (n = 34). In relation to its dimensions, in depression the normal level predominated with 27% (n = 55), in anxiety the normal level predominated in 24% (n = 49), in stress the mild level predominated with 25.5 % (n = 52). Conclusions: According to the mental health of the patients, the normal level prevailed followed by moderate severe, severe, mild and extremely severe. In the depression and anxiety dimension the normal level predominated, and the mild level predominated in stress.